Mental Health Factors associated with North Korean Defectors' Quality of Life - 노인숙; 강희영; 전중희 (International Journal of Advanced Culture Technology(IJACT), 2019)
The purpose of this study was to assess mental health and quality of life (QOL) including factors influencing QOL among early North Korean defectors in South Korea. Participants were 151 early North Korean defectors residing in a settlement support center. All measures were self-administered. Unlike refugees living in communities, early defectors did not experience a high rate of mental health problems and reported a good QOL. Psychoticism was the most predictive factor affecting QOL. Findings from this study suggest the importance of mental health assessment and support over time. Psychoticism, significant in explaining QOL of early North Korean defectors, needs early diagnosis and treatment to prevent progression. Mental health issues among refugees may not be evident while they are in a structured, supportive environment. Evaluation and treatment are needed over time.